2021
DOI: 10.23954/osj.v6i1.2811
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephritis; Pathogenesis and Treatment Update Review

Abstract: Lupus nephritis (LN) is a serious complication of systemic lupus erythematosus (SLE). LN is a leading cause of morbidity and mortality in SLE patients. LN presents with various symptoms and signs, ranging from asymptomatic renal involvement to End-Stage Renal Failure (ESRD). The pathogenesis of LN is not clearly understood, however, there are extra and intra-renal underlying factors that have been postulated in LN pathogenesis. Renal biopsy is crucial to stage LN and to rule out other causes. Histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Among these factors, SLE, simply called lupus, is one of the most significant causes of nephritis, which is known as lupus nephritis (LN). In fact, sedimentation of inflammatory mediators in the kidney tissue as the main result of SLE leads to glomerulonephritis and tubulointerstitial inflammation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these factors, SLE, simply called lupus, is one of the most significant causes of nephritis, which is known as lupus nephritis (LN). In fact, sedimentation of inflammatory mediators in the kidney tissue as the main result of SLE leads to glomerulonephritis and tubulointerstitial inflammation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have confirmed that the activation of nuclear factor kappa B (NF- κ B) signal pathway via upregulation of proinflammatory mediators such as cyclooxygenase-2 (COX-2) and tumor necrosis factor- α (TNF- α ) is responsible for LN [ 13 ]. Also, it has been demonstrated that B- and T-cell hyperactivity [ 14 ], increased T helper 1 (Th1) and T helper 17 (Th17) cytokines [ 15 , 16 ], activation of JAK/STAT-3 signaling [ 17 ], elevation of anti-double-stranded DNA (anti-dsDNA) antibodies [ 12 ], autoantibodies against proteins involved in clearing extracellular nuclear material such as pentraxin 3 or C-reactive protein [ 18 ], interleukin-6 (IL-6), interleukin-17 (IL-17), interleukin-23 (IL-23), TNF- α [ 19 , 20 ], oxidative stress [ 14 ], decreased T regulator cells (Tregs) [ 21 ], and complement system [ 22 ] play important roles in the pathophysiology of LN.…”
Section: Introductionmentioning
confidence: 99%